Geneticheskaya i psikhofizicheskaya determinatsiya kvantogo-polevogo urovnya bioenergetiki organizma sportsmenov - Bundzen, P. V.; Zagrantsev, V. V.; Nazarov, I. B.; Rogozkin, V. A.; Kolodij, O. V.; Korotkov, K. G. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The results of the complex research of the diagnostic importance of the parameters of a quantum-field level of bio-energetics of an organism for definition of phychophysical potential are represented in this article. Methods were used: the computer electrography caused energoemission processes (CEEP); the molecular-genetic analysis - definition of a genotype; functional testing of cardioresperative endurance and definition of the phychoempotional status of examinees. The data was processed by methods of multipleparameter statistics. Researches were carried out on 40 elite athletes and 29 students specializing in track and field athletics. The analysis of the received data has shown, that CEEP parameters find out dependence as from the genetic factor determining the quality of endurance to physical loads, and from phychophysical potential changes during training activity. The materials of researches testify the expediency of use of the parameters reflecting the condition of the quantum-field level of bio-energetics to forecast the functional reserves of an organism of the person and the specific features of the adaptation to the extreme conditions of activity.